Analysis Influence Fintech Payment and Financial Literacy Management Finance with Behavior Consumptiveness and Self-Efficacy as Variables Mediation in Gen Z Regency Jepara - Hanif nugroho, Mohammad; Anna Widiastuti; ali (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes the effect of fintech payments and financial literacy on financial management, with consumptive behavior and self-efficacy as mediating variables among Generation Z in Jepara Regency. Using a quantitative survey approach, data were collected from 145 Generation Z respondents aged 17–27 years who had used fintech payment services. Data were analyzed using SEM-PLS with SmartPLS 3.29. The results show that fintech payments affect consumptive behavior and self-efficacy but not financial management directly. Financial literacy affects financial management and consumptive behavior. Consumptive behavior and self-efficacy mediate the effect of fintech payments on financial management. Keywords: Fintech payment; financial literacy; financial management; consumptive behavior; self-efficacy; Generation Z